Female nesting behaviour affects hatchling survival and sex ratio in the loggerhead sea turtle: implications for conservation programmes. Issue 2 (4th March 2018) - Marco, Adolfo; Abella, Elena; Martins, Samir; López, Oscar; Patino-Martinez, Juan
Abstract : Nest-site selection and the depth at which turtle females deposit their eggs have a decisive influence on temperature in the nest chamber. Thus, female turtle nesting behaviour can influence the sex, fitness and emergence behaviour of their hatchlings. We studied nest-site selection and nest depth in 333 natural loggerhead ( Caretta caretta ) nests from a nesting population in Cabo Verde. Nest site and depth varied among females and among different nests from the same female. However, female body size only explained a very small part of the variability of nest depth. Nest incubation temperature also varied as a function of depth. To test the influence of nest depth on incubation and embryonic development, 90 loggerhead nests were incubated in standard conditions and at different depths (35, 40, 45, 50 and 55 cm) in a beach hatchery and monitored until hatching. Deeper nests had greater emergence success and lower temperature, and hatched later, affecting hatchling sex ratio. Incubation at 35 cm can lead to 89.4–97.7% females, whereas incubation at 50 cm would produce around 62.4–64.9% females. Survival in nests at 35 cm was lower than at deeper nests. Female turtles that dig deeper nests may have more vigorous offspring, exhibiting faster locomotor abilities. Nest depth did not influence emergence behaviour. However, clutch size enhanced synchrony at emergence, resulting in a higher number of hatchlings emerging simultaneously in smaller nests. Depth at which nests are re-buried should be considered a key factor for the success on nest relocation programmes. Females could reduce the impact of climate warming on embryonic development by nesting at deeper locations.